Anemia and Interleukin-10, Tumor Necrosis Factor Alpha, and Erythropoietin Levels among Children with Acute, Uncomplicated Plasmodium falciparum Malaria - Nussenblatt, Veronique (American Society for Microbiology, 2001)
Anemia is an important complication of malaria, and its pathogenesis is not well understood. To gain insight into potential age-related relationships between tumor necrosis factor alpha (TNF-α), interleukin 10 (IL-10), erythropoietin, and anemia during acute malaria, 273 children of ages 12 to 120 months presenting with acute, uncomplicated malaria in Kampala, Uganda, were monitored at enrollment and 3 and 7 days later. Younger children had higher geometric mean erythropoietin, TNF-α, and α(1)-acid glycoprotein (AGP) concentrations than older children. Univariate regression analysis revealed that age, log(10) erythropoietin levels, IL-10/TNF-α ratio, and AGP levels were each significantly associated with hemoglobin levels at baseline. Hemoglobin concentrations were inversely correlated with the log(10) erythropoietin level at all three visits. For the older age groups, higher levels of TNF-α were significantly associated with higher IL-10 levels at all three visits, but this relationship was significant only at baseline for younger children. These data suggest that younger children do not maintain IL-10 production in response to the inflammatory process, and this mechanism may contribute to the more severe anemia found in younger children. Acute malaria is an illness whose incidence and severity are largely age dependent. Further studies are needed to understand the relationships between age-related immune responses to malaria and their role in the pathogenesis of malarial anemia.